Komposit Bioactive Glass Berbasis Silika Abu Ampas Tebu dan Gum Mimba Menstimulasi Proses Remineralisasi Permukaan Gigi - Indahyani, Didin Erma; Barid, Izzata; Verawati, Verawati (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2024)
Dentin hypersensitivity results from exposed dentinal tubules. One of the treatments used is remineralization of dentin and cementum. Bioactive glass (BAG) is a material that can stimulate the remineralization process due to its silica content. Sugarcane bagasse contains high levels of silica and is used as a BAG material. Adding binders and emulsifiers to paste forms increases bonding and stability and makes application easier. Neem gum is a polysaccharide, has emulsifying properties, and can unite two or more ingredients with different properties, increasing the strength of the ingredients. The study aims to analyse the effect of neem gum and bioactive glass composites based on silica bagasse ash on tooth remineralisation. There were three research groups, namely control (BAG paste), treatment A (hyaluronic acid BAG paste) and treatment B (BAG paste, hyaluronic acid and neem gum). The injection paste was applied to the teeth [using cow teeth] on the mesial surface, then soaked in artificial saliva for six days and stored in an incubator at 370C. The remineralization process was observed by forming hydroxycarbonate apatite (HCA) on the tooth root surface using a scoring method based on the Scanning Electron Microscope (SEM) results. CA formation in the BAG, hyaluronic acid and neem gum composite group had a significantly (p<0.05) higher HCA formation score than the group without gum. The control group experienced a washout, so no HCA was formed. BAG composite paste with silica based on bagasse ash and neem gum stimulates the remineralization process marked by the formation of HCA on the tooth root surface.